Robinah: A Dignified Women in the Dutch East Indies in Dutch Colonial Era - Izzah, Latifatul; Ariwidodo, Eko; Subaharianto, Andang; Krisnadi, IG.; Suharto, Suharto; Afiah, Neneng (KARSA Journal of Social and Islamic Culture, 2023)
Dutch colonialism from 1860 to 1935 witnessed a prevalent phenomenon of indigenous women in the Dutch East Indies entering into concubinage arrangements with European men, often assuming the position of â€œnyaiâ€ (mistresses) due to various socioeconomic factors. This study explores whether this situation was universal among indigenous women by examining the case of Robinah, who achieved an esteemed status during this era. Utilizing feminist theory and historical research methodologies, the investigation analyzes primary and secondary sources related to the Regentschap Bondowoso region in East Java. The research reveals that Robinah, a woman of Madurese descent, became the legitimate wife of Dutch investor George Birnie, diverging from the typical concubinage model. Robinah's intellectual acumen and communicative prowess were crucial in expanding Birnie's tobacco plantation enterprise, facilitating labor acquisition and land management within the predominantly Madurese local community. This case exemplifies how certain relationships between Dutch men and indigenous women could transcend the conventional concubinage paradigm, resulting in more egalitarian partnerships and enhanced social standing for the indigenous women involved. The study contributes to the scholarly discourse on the intricate dynamics of cross-cultural relationships and female agency within colonial contexts. Navigating mixed marriages can be challenging due to family resistance and social pressures, which can hinder the couple's integration into each other's groups. Sociological research examining power dynamics and identity in these unions is crucial for understanding their impact on social change and harmony and overcoming these obstacles.